Harnessing sodic groundwater for sustainable crop production: Synergistic effects of drip irrigation, gypsum and mulch in rice (Oryza sativa)–wheat (Triticum aestivum) cropping system - MEENA, BABU LAL; FAGODIYA, RAM KISHOR; SINGH, AWTAR; NARJARY, BHASKAR; KALEDHONKAR, M J; SHEORAN, PARVENDER; KUMAR, SATYENDRA; YADAV, R K (The Indian Journal of Agricultural Sciences, 2026)
A three-year field experiment (2020–23) was conducted at Budhmor village, Patiala district, Punjab, to evaluate the judicious use of sodic groundwater through drip irrigation, gypsum and mulch in a rice (Oryza sativa L.)–wheat (Triticum aestivum L.) cropping system (RWCS). The study followed a split-split plot design with three irrigation regimes (80% and 100% of ETc through drip and conventional flood), three gypsum levels (0, 25 and 50% gypsum requirement) and two mulch treatments (with and without crop residue). Drip irrigation significantly reduced soil pH (8.66) compared to flood irrigation (9.19) due to enhanced leaching of soluble sodium. Gypsum application further lowered soil pH to 8.51 and improved organic carbon, nitrogen, phosphorus and potassium availability. The interaction between drip irrigation and gypsum (I₁G₃) produced the highest soil organic carbon (0.65%), available nitrogen (165.07 kg/ha), phosphorus (25.70 kg/ha) and potassium (215 kg/ha). Wheat yield increased from 29.94 q/ha under flood irrigation to 48.26 q/ha under I₁G₃, while direct-seeded rice (DSR) yield was 30.80 q/ha under similar conditions. Gypsum significantly improved chlorophyll content in both crops, indicating enhanced physiological performance. Mulching had positive but non-significant effects on most parameters. Overall, the integrated use of drip irrigation at 80% ETc with 50% gypsum requirement was found most effective in mitigating sodicity, improving soil fertility and sustaining crop productivity under sodic groundwater irrigation in the Indo-Gangetic Plains.